Empirical likelihood ratio for two-sample compound Poisson processes under infinite second moment. Issue 11 (3rd June 2022) - Cheng, Conghua
Abstract: In this article, the author focus on the simple and yet very important case of making inference on the difference of two population means using the empirical likelihood approach of two sample compound Poisson process under infinite second moment. It is shown that the log empirical likelihood ratio statistic for the difference of two population means converges in distribution to χ ( 1 ) 2 as n → ∞ . The simulation results show that the empirical likelihood ratio method is applicable under infinite second moment.